Design and implementation of heterogeneous surface gateway for underwater acoustic sensor network - Youngjun Jo; Sangsoon Lim (Institute of Advanced Engineering and Science, 2019)
Underwater Acoustic Sensor Networks (UASNs) are used for diverse purposes such as pollution monitoring, disaster prevention and industrial sensing in the oceans. Especially, UASNs are mainly focusing on monitoring various underwater environmental data and delivering the data to a monitoring center where nearby or far from the deployed area. To reliably deliver the data, a surface gateway should convert acoustic signal to RF (Radio Frequency) signal. In this paper, we devise a multiple interfaces-based surface gateway that can connect both a cellular network and a Zigbee network. Depends on the service requirement, the surface gateway can easily adopt each wireless interface and relay the data to a low power ZigBee network or a long range CDMA network.